The role of ‘green’ courts in shaping environmental justice in India and New Zealand - Kowalska, Samanta (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The depreciation of values, combined with the expansion of agriculture, industry and the economy, results in the erosion of existing protection mechanisms, as well as commodification and dominance of economic factors. The increasing degradation of the natural environment reveals an increasing number of areas requiring urgent and coordinated protection. The aim of the article is to present the innovative concept of green courts, which are creating a new architecture of modern environmental law. In the considerations, it is indicated that ‘green’ courts at a national level open the way to formulate new legal institutions, facilitate more effective the enforcement of environmental law, and solve legal disputes with alternative adjudicative processes. The article discusses environmental justice based on the example of India and New Zealand, which are among the first countries in the world to have developed an innovative judicial structure and environmental case law. The dogmatic method plays an essential role in the analysis of legal norms concerning the protection of environment, as well as in determining their content and scope. The source materials originate from various legal orders, and diverse cultural and geographical regions. Therefore, in order to discuss the indicated issues, it is necessary to use the comparative method, and thus complete the arguments of a dogmatic and legal nature. In order to present the origins and evolution of law in the scope concerning ‘green’ courts, the historical and legal method is used (temporal retrospection). The considerations emphasize the role of specialist ‘green’ courts in maintaining a balance between the economy, the development of society, and protecting the environmental wellbeing by shifting the focus of jurisprudence to the environmental domain. The article highlights the role of the application and interpretation of environmental norms from an ethical and intergenerational perspective.